2017
DOI: 10.1021/acscatal.7b02144
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of the Mn Promoter via CoMn Spinel for Morphology Control: Formation of Co2C Nanoprisms for Fischer–Tropsch to Olefins Reaction

Abstract: The Fischer–Tropsch to olefins (FTO) reaction over Co2C catalysts is structure-sensitive, as the catalytic performance is strongly influenced by the surface structure of the active phase. The exposed facets determine the surface structure, and it remains a great challenge to precisely control the particle morphology of the FTO active phase. In this study, the controlling effect of the Mn promoter on the final morphology of the Co2C nanoparticles for the FTO reaction was investigated. The unpromoted catalyst an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
82
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 85 publications
(86 citation statements)
references
References 39 publications
4
82
0
Order By: Relevance
“…For the reduced Co 3 O 4 catalyst without Mn addition, the peaks were mainly attributed to Co 0 and CoO (Figure a). Besides, the results for the spent Co 3 O 4 sample revealed that only Co 2 C phase at 2θ of 37.0°, 41.3°, 42.6°, 45.7° and 56.6° could be detected (Figure b), suggesting that Co species were all transformed into Co 2 C. However, all the reduced CoMn samples showed the characteristic peak of Co x Mn 1‐x O phase (Figure a), which was the precursor for the formation of Co 2 C nanoprisms . For the spent Co3Mn1, Co2Mn1 and Co1Mn1 catalysts, both MnCO 3 and Co 2 C phase co‐existed.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…For the reduced Co 3 O 4 catalyst without Mn addition, the peaks were mainly attributed to Co 0 and CoO (Figure a). Besides, the results for the spent Co 3 O 4 sample revealed that only Co 2 C phase at 2θ of 37.0°, 41.3°, 42.6°, 45.7° and 56.6° could be detected (Figure b), suggesting that Co species were all transformed into Co 2 C. However, all the reduced CoMn samples showed the characteristic peak of Co x Mn 1‐x O phase (Figure a), which was the precursor for the formation of Co 2 C nanoprisms . For the spent Co3Mn1, Co2Mn1 and Co1Mn1 catalysts, both MnCO 3 and Co 2 C phase co‐existed.…”
Section: Resultsmentioning
confidence: 99%
“…As for pure Co 3 O 4 , Co 0 and CoO phases were observed after reduction, while Co x Mn 1‐x O could be obtained after introducing Mn into Co‐based catalysts. Our previous work has already demonstrated that the Co x Mn 1‐x O spinel phase played a vital role for the formation of Co 2 C nanoprisms with exposed (101) and (020) facet . The absence of Mn promoter for Co 3 O 4 caused the formation of Co 2 C nanospheres with (111) as dominant facet via carburization of Co 0 and CoO route, which restrained the CO dissociation and favored the production of methane.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[67] These authors found that MnO x affects the formation of Co 2 C, ap hase which has been recently shown to have ah igh selectivity towards lower olefins. [68] In our current work, it was furtherf ound that by doping a 5Co5Fe2.5Mn/g-Al 2 O 3 material with additional 1.2 wt.% of Na and 0.03 wt.% of S, the selectivity towards C 4 olefins could be significantly improved, whereas, compared to the Na/S-free catalysts, C 5 + and CH 4 fractionsa re reduced at ac omparable C 4 olefin productivity of 0.03 kg·kg cat À1 ·h À1 .F urthermore, the Na/S ratio has been identified as af actor influencing the isomerization of 1-alkenes. Thus, by adding Na as ap romoter,t he isomerization of 1-alkenes can be inhibited and the ratio of 1alkenes to internal and iso-alkenes is maintainede ven if Si s present.I no ther words, under S-rich conditions, the selectivity can be directed towards the target product 1-butene as the primary product in the C 4 olefin fraction and therefore the amount of waste streams that need to be recycled, treated or upgraded is reduced.…”
Section: Resultsmentioning
confidence: 99%